Documentation and analysis of traumatic injuries in clinical forensic medicine involving structured light three-dimensional surface scanning versus photography. (August 2018) - Shamata, Awatif; Thompson, Tim
Abstract: Non-contact three-dimensional (3D) surface scanning has been applied in forensic medicine and has been shown to mitigate shortcoming of traditional documentation methods. The aim of this paper is to assess the efficiency of structured light 3D surface scanning in recording traumatic injuries of live cases in clinical forensic medicine. The work was conducted in Medico-Legal Centre in Benghazi, Libya. A structured light 3D surface scanner and ordinary digital camera with close-up lens were used to record the injuries and to have 3D and two-dimensional (2D) documents of the same traumas. Two different types of comparison were performed. Firstly, the 3D wound documents were compared to 2D documents based on subjective visual assessment. Additionally, 3D wound measurements were compared to conventional measurements and this was done to determine whether there was a statistical significant difference between them. For this, Friedman test was used. The study established that the 3D wound documents had extra features over the 2D documents. Moreover; the 3D scanning method was able to overcome the main deficiencies of the digital photography. No statistically significant difference was found between the 3D and conventional wound measurements. The Spearman's correlation established strong, positive correlation between the 3D and conventional measurement methods. Although, the 3D surface scanning of the injuries of the live subjects faced some difficulties, the 3D results were appreciated, the validity of 3D measurements based on the structured light 3D scanning was established. Further work will be achieved in forensic pathology to scan open injuries with depth information. Highlights: Structured light 3D surface scanning outdoes the main deficits of the photography. 3D models of wound have extra features over 2D photos. No significant difference between traditional and 3D wound measurements. There is strong positive correlation between traditional and 3D wound measurements.